Pengembangan Penuntun Praktikum Biologi dengan Pendekatan Kontekstual Berbasis Inkuiri Terbimbing pada Materi Jamur Kelas X MIPA SMA Negeri 5 Jeneponto - Siska Nurul Avisha; Nurul Magfirah; Nurul Fadhilah (Politeknik Kampar, 2025)
The aim of this research is to determine the validity and practicality of a guided inquiry-based Biology practicum guide with a contextual approach to the material on Mushrooms for class X MIPA. This research is Research and Development (R&D) which adopts the 4D development model which is modified to 3D (Define, Design, Development). The population in this study were students of class X MIPA 1 SMA Negeri 5 Jeneponto. The data collection technique was by using a validity and practicality assessment questionnaire. The data collected were data on the validity and practicality of the developed practicum guide. The results of the validity analysis showed that the Biology practicum guide that had been developed obtained a value of 0.82 which was in the valid category. While the results of the practicality analysis were in the range of values> 47.6 with a percentage of 100% of respondents, namely teachers and students, saying that the practicum guide was in the practical category so that it could be concluded that the biology practicum guide based on guided inquiry with a contextual approach on the Mushroom material in class X MIPA was valid and practical.